Job satisfaction moderates the effect of competence and training on employee performance, a study on SMEs members of the Intako in Cooperative Sidoarjo Regency - Kusworo, Ahmad Dzulfikri Budi; Budiyanto, Budiyanto; Suwitho, Suwitho (Indonesian Journal Publisher, 2024)
This research is entitled